BODIPY–Tetrazine Derivatives as Superbright Bioorthogonal Turn‐on Probes1. Issue 27 (27th May 2013) - Carlson, Jonathan C. T.; Meimetis, Labros G.; Hilderbrand, Scott A.; Weissleder, Ralph
<x xml:space="preserve">Abstract</x> The fastest and the brightest: A new design that intimately connects tetrazine to a BODIPY fluorophore enables exceptionally efficient energy transfer and quenching. Upon reaction of the tetrazine, the brightness of the fluorophore increases more than a thousand‐fold, which is a fluorogenic activation up to two orders of magnitude greater than previously described.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>